Arecoline Induces an Excitatory Response in Ventral Tegmental Area Dopaminergic Neurons in Anesthetized Rats - Lan, Qinghui; Guan, Peiqing; Huang, Chunzheng; Huang, Shile; Zhou, Peiling; Zhang, Changzheng (Frontiers in Pharmacology, 2022)
Arecoline is the principle psychoactive alkaloid in areca nuts. Areca nuts are chewable seeds of Areca catechu L., which are epidemic plants that grow in tropical and subtropical countries and cause dependency after long-term use. However, the mechanisms underlying such dependency remain largely unclear, and therefore, no effective interventions for its cessation have been developed. The present study aimed to examine the effects of arecoline on neurons of the ventral tegmental area (VTA). After rats were anesthetized and craniotomized, electrophysiological electrodes were lowered into the VTA to obtain extracellular recordings. The mean firing rate of dopaminergic and GABAergic neurons were then calculated and analyzed before and after arecoline treatment. The burst characteristics of the dopaminergic neurons were also analyzed. The results showed that arecoline evoked a significant enhancement of the firing rate of dopaminergic neurons, but not GABAergic neurons. Moreover, arecoline evoked remarkable burst firings in the dopaminergic neurons, including an increase in the burst rate, elongation in the burst duration, and an enhancement in the number of spikes per burst. Collectively, the findings revealed that arecoline significantly excited VTA dopaminergic neurons, which may be a mechanism underlying areca nut dependency and a potential target for areca nut cessation therapy.